2018
DOI: 10.1002/tee.22845
|View full text |Cite
|
Sign up to set email alerts
|

The effect of citrus ginger aroma on heart rate and salivary cortisol level during sleep at home

Abstract: The aim of this study is to investigate the effect of odor on the heart rate (HR) and salivary cortisol levels during sleep at home. Twenty male students (aged 20.9 ± 0.74 years) participated in the study and were exposed to three different odorants (apple, cedar wood, and citrus ginger) or a scentless control sample each night in their home environment in a counterbalanced order. In this within-subjects study design, all subjects were instructed to sleep at home for 6 h, from 00:00 to 06:00, and HR was measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…7). Often, studies (59/179, 33%) identified the wearable as innovative, that is, as a cutting-edge tool and method [103] with a wearable device potentially closing a gap in or improving health care and research. For example, 1 study described how wireless wearables and data synching could improve the quality of care [69], "The data can be sent from the wearable to the physician's office, avoiding the need for office visits, ultimately making possible preventive medicine and improving quality of care."…”
Section: Othersmentioning
confidence: 99%
“…7). Often, studies (59/179, 33%) identified the wearable as innovative, that is, as a cutting-edge tool and method [103] with a wearable device potentially closing a gap in or improving health care and research. For example, 1 study described how wireless wearables and data synching could improve the quality of care [69], "The data can be sent from the wearable to the physician's office, avoiding the need for office visits, ultimately making possible preventive medicine and improving quality of care."…”
Section: Othersmentioning
confidence: 99%
“…It uses different types of essential oils, and various psychological and physiological effects are expected from these aromas. Previous studies on aromatherapy have reported reduced anxiety with lavender [ 1 , 2 ], orange [ 3 6 ], sandalwood [ 7 ], citrus ginger [ 8 ], Hiba [ 1 ], and Melissa officinalis (lemon balm) extract [ 9 ]; relieved stress with lemon [ 10 ], peppermint [ 11 ], black tea [ 12 ], green tea [ 13 ] and blended essential oil with sandalwood and lavender [ 14 ]; improved sleep quality with lavender [ 2 , 15 , 16 ] and Rosa damascene [ 17 ]; induced physiological relaxation with Hinoki cypress leaf oil [ 18 ], and increased memory performance with lavender, rosemary [ 19 ], and ginger [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inhalation of ginger essential oil has demonstrated positive effects on nausea and vomiting severities [21][22][23] and ginger oil massage has been effective in relieving chronic low back pain [24] and moderate-to-severe knee pain [25] in older adults, while ginger extract showed positive efficacy in pain relief and improved functionality in patients with moderate knee osteoarthritis [26]. Moreover, inhalation of citrus ginger during sleep enhanced sympathetic nervous system (SNS) activity upon awakening and alleviated psychological tension and anxiety [8].…”
mentioning
confidence: 99%
“…First, after inhaling essential oils, the nasal olfactory nerve carries the scent information to the rhinencephalon (the olfactory area of the brain), which can trigger the rapid release of neurotransmitters (such as dopamine and 5-HT) that regulate the nervous system. This can induce physiological and mental states of relaxation, pleasure, and happiness [1][2][3][4]. Second, after inhaling essential oils, essential oil molecules can enter the nasal mucosa and lungs.…”
Section: Introductionmentioning
confidence: 99%
“…E-mail: xuemei_bai@yahoo.com blood circulation or are recognized by olfactory epithelium-specific gas receptors. The scent information is then transmitted to the olfactory bulb through the olfactory sensing potentiometer, where it can activate the limbic brain system or the brain stem network to affect mood, memory, cognition, behavior, or physiology [1,5].…”
Section: Introductionmentioning
confidence: 99%